Carbon nanowall-based nanocomposites synthesised by HF-PECVD for photoelectrochemical applications / Noor Hamizah Khanis - Noor Hamizah , Khanis (2019)
Carbon nanowalls (CNWs) are known as two dimensional nanostructures which consist of stacked graphene sheets standing vertically on the substrates. Due to its large area to volume ratio and thin edges perpendicular to the substrates, CNW structures emerge as one of the promising electrode materials for electrochemical devices specifically for photoelectrochemical (PEC) application. The main objective of this work is to grow applicable vertically aligned CNW by hot filament plasma enhanced chemical vapour deposition (HF-PECVD) and to decorate the surface with tin oxide (SnO2) and zinc oxide (ZnO) nanoparticles forming SnO2/CNW and ZnO/CNW nanocomposites, respectively. Gold nanoparticles were deposited on SiO2 substrate by drop-cast method to act as catalyst. In this work, the important HF-PECVD parameters required to grow CNW structures such as applied radio frequency (rf) power, substrate temperature, deposition pressure and deposition duration were studied to understand the growth model of the CNW structures. It is observed that the applied rf power significantly affect the initial CNW growth while the variation in substrate temperature determines the size and shape of Au catalyst, thus leading to different morphologies of CNW. Meanwhile, the deposition pressure and deposition duration were used to study the progression of CNW growth. The morphology, structural and chemical composition of the films were investigated by field emission scanning electron microscopy, high resolution transmission electron microscopy, Raman and X-ray photoelectron spectroscopies. The CNW films with the most suitable morphologies and characteristics for the preparation of nanocomposite were obtained at rf power of 80 W, substrate temperature of 420 oC, deposition pressure of 2.2 mbar and deposition duration of 35 minutes. Using these iv parameters, CNW with the characteristics with high surface to volume ratio, vertically-oriented carbon nanosheets, non-stacking morphology and exposed edges were obtained. The growth mechanism of the CNW was stipulated based on the parameters studied based on Gibbs-Thomson effect. Subsequently, SnO2 and ZnO nanoparticles were decorated onto this optimized CNW structures at different concentration of 2.5, 5.0 and 7.5 wt%. The morphology, structural, chemical bonding composition, optical and electrochemical properties were then investigated to determine the potential of these nanocomposites as electrode material in electrochemical devices. Both of the SnO2/CNW and ZnO/CNW nancomposites obtained from 5.0 wt% metal oxide concentration exhibit enhanced photocurrent density of 11.8 and 17.1 mA/cm2, respectively. Furthermore, as compared to their corresponding single-material metal oxides, the PEC behaviour of these nanocomposite show vast improvement, even when compared to the literature reports of other types of nanostructured carbon-based nanocomposite.